Criminal Procedure. General Part : manual - Торбас, Олександр Олександрович; Torbas, Oleksandr O.; Торбас, О. О.; Степаненко, Андрій Сергійович; Stepanenko, Andrii S.; Степаненко, А. С.; Мурзановська, Аліна Владиславівна; Murzanovska, Alina V.; Мурзановська, А. В. (Odessa : Feniks, 2022)
The manual is designed for students of Criminal Procedure course for preparation to lessons and self-study. The manual consists of synopsis of the lectures course, seminar programme with questions and reading sections, questions for exam preparation and learning resources. It would be helpful for legal scholars, students, legal practitioners and anyone interested in criminal process of Ukraine.

Посібник призначений для студентів курсу Кримінальний процес, для підготовки до занять та самонавчання. Посібник складається з конспекту курсу лекцій, програми семінарського заняття с питання та розділи для читання, запитання для підготовки до іспиту та навчальні ресурси. Буде корисним для вчених-юристів, студентів, юристів-практиків та всіх, хто цікавиться кримінальним процесом України.
Torbas A. V. Criminal Procedure. General Part : manual [Electronic edition] / A. V. Torbas, A. S. Stepanenko, A. V. Murzanovskaya. – Odessa : Feniks, 2022. – 129 p. – Режим доступу: https://doi.org/10.32837/11300.18759
Keywords: The concept, objectives, principal institutes of criminal procedure and system of criminal proceedings of Ukraine; сriminal procedural law of Ukraine; principles of criminal proceedings; actors of criminal proceedings; evidence and proving in criminal proceedings; Поняття, завдання, основні інститути кримінального процесу та система кримінального судочинства України; кримінально-процесуальне право України; принципи кримінального судочинства; фігуранти кримінального провадження; докази та доказування у кримінальному провадженні; Research Subject Categories::LAW/JURISPRUDENCE::Criminal law